2022
DOI: 10.3389/fsufs.2022.1022410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water-user performance in smallholder irrigation schemes in KwaZulu-Natal Province, South Africa: A stochastic meta-frontier analysis

Abstract: Smallholder Irrigation Schemes (SIS) are pivotal in sustaining livelihoods and creating employment in rural communities of South Africa. However, despite the revitalization and rehabilitation of SIS by the government, the performance of farmers is still below par. This study evaluates the performance of water-users across four SIS in KwaZulu-Natal Province (KZN). Technical Efficiency was used as a proxy for performance and the Stochastic Meta-Frontier Analysis method was employed to measure the overall efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A study by Phali et al (2022) evaluated the performance of water users across four smallholder irrigation schemes in South Africa and found that governance index, psychological capital, land tenure security, credit access and gender effects were important. Another study by Adams et al (2020), which measured the technical, economic and allocative efficiency of small-scale vegetable farmers practising various irrigation technologies in northern Ghana, found that approximately 27% of the farmers were technically efficient, while 3.6% were found to be both economically and allocatively efficient.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Phali et al (2022) evaluated the performance of water users across four smallholder irrigation schemes in South Africa and found that governance index, psychological capital, land tenure security, credit access and gender effects were important. Another study by Adams et al (2020), which measured the technical, economic and allocative efficiency of small-scale vegetable farmers practising various irrigation technologies in northern Ghana, found that approximately 27% of the farmers were technically efficient, while 3.6% were found to be both economically and allocatively efficient.…”
Section: Introductionmentioning
confidence: 99%